Cytofluorometric characteristics of molecular subtypes of breast cancer - L. K. Tsoi; V. N. Bogatyrev; I. V. Vysotskaya; V. P. Letyagin; E. A. Kim (ABV-press, 2014)
The paper deals with the results of a study assessing the specific data of laser DNA-flow cytofluorometry and the level of mutant p53 in different histogenetic subtypes.